Modification and mechanical properties of electrospun blended fibermat of PLGA and siloxane-containing vaterite/PLLA hybrids for bone repair (eXPRESS Polymer Letters, 2011)
Multi-syringe electrospinning has been successfully employed to produce a blended fibermat composed of poly(lactic-glycolic acid) (PLGA) fibers and a composite fiber for bone repair. The composite fiber, siloxane-containing vaterite (SiV)/poly(L-lactic acid) (PLLA), donated as SiPVH has the ability to release soluble silica species and calcium ions at a controlled rate. The SiPVH fibermats have demonstrated excellent bone regeneration ability in vivo at the front midline of the calvaria of rabbits. However, they are brittle and have low tensile strength resulting from the large particulate SiV (60 wt%) content. In this study, co-electrospinning of PLGA with SiPVH was performed in the hope of achieving a blended fibermat with improved mechanical properties. The co-electrospun fibermats showed good homogeneous blending of the PLGA and SiPVH composite fibers that had excellent flexibility. The blended PLGA-SiPVH fibermats had significantly improved mechanical properties compared to the SiPVH fibermats, where more than 20 times higher elongation to failure was achieved on comparison to the SiPVH fibermat. As well as strength, high porosity and large pore size are vital for the migration of cells into the centre of the graft. This was accomplished by heating the PLGA-SiPVH fibermats at 110°C for a fixed time, which induced the softening and flow of PLGA towards the more stable SiPVH fibers. Heating had successfully produced PLGA-SIPVH fibermats with large open pores and inter-fused SiPVH fibers, which also had better tensile mechanical properties than the SiPVH fibermat.